The Oriental genera of Xyloperthini (Coleoptera: Bostrichidae: Bostrichinae), with a new genus and species from Thailand, and a key to the genera - Liu, Lan-Yu; Sittichaya, Wisut (European Journal of Taxonomy, 2022)
We describe a new genus, Infrantenna gen. nov. and a new species Infrantenna fissilis gen. et sp. nov., from Thailand and briefly review the Oriental genera currently placed in the tribe Xyloperthini Lesne, 1921. A key to the Oriental genera of Xyloperthini is provided.